Inclusion and Belonging in Cities of Tomorrow Governance and Access by Design - Pineda, Victor Santiago (Springer Nature Singapore : Imprint: Palgrave Macmillan, 2024)
"The rapid spread of smart cities around the world has the potential to deepen inequality and accelerate inclusion and belonging. In his powerful and timely new volume, Dr. Victor Pineda calls on city leaders and residents to adopt a radically inclusive approach to urban design in a digitally transforming world." -Robert Muggah, PhD, Smart city expert and TED speaker, Founder of SecDev and Igarape Institute, Author of Terra Incognita This open access book uncovers the historical context and entrenched beliefs that have perpetuated exclusionary urban landscapes and disadvantage for marginalized groups. It offers an in-depth exploration of the intricate interplay of geographical space, recognizing its pivotal role in shaping our cities and exacerbating spatial injustice. The construction industry, a vital agent in forging accessible environments, often falls short in accommodating persons with disabilities and older individuals. This important book underscores the urgent need for integrated approaches woven into the fabric of cities, companies, and the construction industry itself, to ensure universal accessibility. Drawing upon practical strategies and compelling case studies, the book presents actionable frameworks such as the DisCo Policy Framework and the Iceberg of Inequality Model, facilitating the assessment of progress towards achieving radical inclusion. Inviting readers to embark on a journey into the cities of tomorrow, where inclusion and belonging are the norm, it concludes with a simple idea: the future is accessible. Victor Santiago Pineda is a lecturer in the Department of City and Regional Planning at the University of California Berkeley, USA. He is a two-time presidential appointee and a globally recognized leader on governance and urban transformation. His teaching, research and practice have advanced innovation in urban policy, planning and global governance.